PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV UPT SD NEGERI TALLANG-TALLANG KABUPATEN GOWA - Ramlah, Ramlah; Pada, Amir; Abidah Idrus, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine (1) an overview of the use of the Role-Playing learning method in Pancasila Education for Grade IV at UPT SD Negeri Tallang-tallang, Gowa Regency, (2) an overview of students' learning outcomes in Pancasila Education for Grade IV at UPT SD Negeri Tallang-tallang, Gowa Regency, and (3) the effect of using the Role-Playing method on the learning outcomes of Grade IV students in Pancasila Education at UPT SD Negeri Tallang-tallang, Gowa Regency. This type of research is a quasi-experimental study with a Nonequivalent Control Group Design. The research subjects consisted of two classes, namely Class IVA with 21 students as the experimental class, and Class IVB with 24 students as the control class. Research data were obtained through pre-tests, post-tests, and observations, then analyzed using descriptive and inferential statistics with the t test aided by SPSS software. The results of the study show that (1) the use of the Role Playing method over two meetings led to an improvement in teacher activities from a good category to a very good category, and student activities also increased from a sufficient category to a very good category during the learning process. (2) Students' learning outcomes in the Pancasila Education subject also improved, as evidenced by the post-test scores of the control class falling into the moderate category, while the post-test scores of the experimental class were in the very high category. (3) There is an effect of using the Role Playing method on the learning outcomes of Pancasila education for fourth-grade students at UPT SD Negeri Tallang-tallang, Gowa Regency, through an Independent Sample t-test using IBM SPSS Statistics, which shows a significance value of 0.001 < 0.05.